Progress in Microalgae Research A Path for Shaping Sustainable Futures - Queiroz Zepka, Leila; Jacob-Lopes, Eduardo; Costa Deprá, Mariany (IntechOpen, 2022)
Progress in Microalgae Research - A Path for Shaping Sustainable Futures consolidates the latest research, developments, and advances in the field of microalgae biotechnology. The book's chapters take a close look at and highlight the wide commercial potential of microalgae-based processes and products. This book is a useful resource for researchers and academic and industry professionals in the field of microalgae biotechnology.